Ambiguitas Leksikal dalam buku Anak -anak Amelia Bedelia Karya Herman Parish - Sabrina Nurul Huda; Nur Utami Sari’at Kurniati; Ni Made Widisanti Swetasurya (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to identify words that contain lexical ambiguity, explore their meanings, and classify them in the children’s book Amelia Bedelia by Herman Parish. The data were collected from the Amelia Bedelia Chapter Books series, which consists of twelve books published between 2013 and 2018. The analysis identified a total of 58 words with lexical ambiguity, including 46 instances of polysemy and 12 of homonymy. The classification of polysemy and homonymy is based on the semantic relatedness or unrelatedness between the multiple meanings of each word. The Amelia Bedelia stories effectively illustrate how children perceive and react to lexical ambiguity through the main character, Amelia, who is known for her literal interpretations of figurative language. This literal understanding often leads to humorous situations. Lexical ambiguity in these books functions not only as a source of entertainment but also as a valuable linguistic learning tool. Therefore, the stories contribute to language development in early childhood readers.